The Effects of Competence, Leadership Style, and Remuneration on Bureaucratic Reform Implementation at The Supreme Court of The Republic of Indonesia - Wifa Diniati; Rina Uswatun Hasanah (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study analyzes the effects of competence, leadership style, and remuneration on the implementation of bureaucratic reform within the Planning and Organization Bureau of the Administrative Affairs Agency of the Supreme Court of the Republic of Indonesia. The study employed a quantitative approach with a cross-sectional survey design. The analysis was based on 60 complete questionnaires that measured competence using five items, leadership style using five items, remuneration using four items, and bureaucratic reform implementation using five items, all rated on a five-point Likert scale. Instrument quality was assessed through item-total correlations and Cronbach's alpha, while the hypotheses were tested using multiple linear regression. To ensure that the inferences were robust to potential heteroskedasticity, the coefficient tests were supplemented with HC3 robust standard errors. The results show that the model explained 86.9% of the variance in bureaucratic reform implementation and was jointly significant (F = 123.757; p < 0.001). Partially, competence had a positive but statistically nonsignificant effect (B = 0.156; p = 0.295), and leadership style also had a positive but nonsignificant effect (B = 0.234; p = 0.121). Remuneration had a positive and significant effect (B = 0.625; p < 0.001) and was the strongest relative predictor. These findings indicate that bureaucratic reform requires integrated human resource management, with an emphasis on a fair, transparent, predictable, and performance-linked remuneration system, without neglecting competence development and change-oriented leadership. The findings should be generalized cautiously because the study focused on a single organizational unit and used perceptual data collected during one observation period.